Cuantificación de biomasa y reserva de carbono en sistemas agroforestales de café (coffea arabica L.) en dos pisos altitudinales - Quiñe Macedo, Paulo César (2009)
This essay entitled "Quantifying Biomass and Carbon Reserve Agroforestry Coffee (Coffea arabica L.) in two levels of altitude," aims to contribute to the generation of information basis for the development of projects for marketing carbon credits, through the use of agro coffee in the Amazon, as sinks of greenhouse gases and as a potential engine of development for coffee producers. We used a descriptive statistics and comparative, which aims to quantify the pool of carbon in agroforestry systems Coffee and two levels of altitude in the San Martín region. These comparisons were made in the E.E. - ICT, located 2.5 km. Tarapoto, in the district Banda of Shilcayo, Sector Venice Lagoon (transects 1, 2, 3), and the Fundo Sananguillo, Sananguillo sector, 10 km. the town of Lamas, in the district of Lamas, Province of Lamas, (transects 4, 5, 6). The results show carbon stocks for each type of biomass and soil in the two plots that were evaluated. In the parcel Fundo's Juan Bernito, the total amount of carbon (biomass and soil) in storage was 119.37 t / ha, where the greatest contribution was the carbon in the soil with 74, 76 t / ha, followed by living trees, dead fallen trees, leaves or mulch and shrub-herbs with 32.85, 5.32, 4.87, 1.89 t / ha respectively. In the Fundo Sananguillo, the amount of carbon stocks was 165.81 t / ha, surpassing the total carbon stored in the Fundo Juan Bernito. The biggest contribution was the carbon in the soil with 114.99 t / ha, followed by the trees alive, dead fallen trees, leaves or mulch, shrubs and herbaceous with 27.83, 17.65, 2.98, 2, 35 t / ha respectively.